2020
DOI: 10.1002/ajmg.a.61875
|View full text |Cite
|
Sign up to set email alerts
|

Etiological diagnosis in limb reduction defects and the number of affected limbs: A population‐based study in the Northern Netherlands

Abstract: Limb reduction defects (LRDs) that affect multiple limbs are considered to be more often heritable, but only few studies have substantiated this. We aimed to investigate if an etiological diagnosis (genetic disorder or clinically recognizable disorder) is more likely to be made when multiple limbs are affected compared to when only one limb is affected. We used data from EUROCAT Northern Netherlands and included 391 fetuses and children with LRDs born in 1981-2017. Cases were classified as having a transverse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
(25 reference statements)
2
15
0
4
Order By: Relevance
“…The characteristics of the limb defects most commonly observed in this study, such as upper limb involvement, longitudinal defects and the radius as the most common affected long bone, are in accordance with previously reported epidemiological studies. 1,4 The overall diagnostic yield in this study was higher in the syndromic group (60.9%) compared to the non-syndromic group (16.7%).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The characteristics of the limb defects most commonly observed in this study, such as upper limb involvement, longitudinal defects and the radius as the most common affected long bone, are in accordance with previously reported epidemiological studies. 1,4 The overall diagnostic yield in this study was higher in the syndromic group (60.9%) compared to the non-syndromic group (16.7%).…”
Section: Discussionmentioning
confidence: 46%
“…A higher diagnostic yield in syndromic forms is well established in the literature, including the study that evaluated a large cohort of 352 individuals with CLD screening 52 genes/regulatory sequences by the same technique applied in our study (targeted NGS), with a positive yield of 43% in the syndromic cases, compared to 26% in isolated forms. 3 Bergman et al, (2020), 1 in an epidemiological study in Northern Netherlands, showed that the involvement of multiple limbs increased the diagnostic yield by three times when compared to the group of individuals with single limb involvement. In the present study, similar data was also observed, with a higher diagnostic yield in the individuals presenting multiple (15/30-50%) compared to single limb involvement (1/5-20%).…”
Section: Discussionmentioning
confidence: 99%
“…LRDs constitute a heterogeneous group of limb defects with variable clinical manifestations and diverse etiologies. Recent progress in molecular biology and genetics enabled the discovery of the molecular basis of selected types of LRDs [29,30]. However, the etiology of the majority of LRDs remains unknown, and several studies highlighted the potential involvement of environmental factors [2][3][4][5]11,12,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The authors cited examples from some pedigrees published by Birch‐Jensen (1949), and several papers show that certain genetic mutations have been associated with reduced limbs. Bergman, Löhner, van der Sluis, Rump, and de Walle (2020) investigated if an etiological diagnosis (genetic disorder or clinically recognizable disorder) is more likely to be made when multiple limbs are affected compared to when only one limb is affected. They used data from Northern Netherlands and included 391 fetuses and children with limb reduction defects born in 1981–2017.…”
Section: Discussionmentioning
confidence: 99%